LITERATURE REVIEW: EFFECTIVENESS OF STRATEGIC MANAGEMENT AND HUMAN RESOURCE MANAGEMENT ON WORKPLACE SAFETY - Elsa Gaotami; Dyah Novenna Reviyanna (OIKONOMIA: Journal of Economics and Management Science, 2023)
In daily lifes it will not be released from the accident word which are harmed even it could be maked the damage until it caused the death. This matters always occured in daily lifes until the people should be careful in order to not let this matter be happen. Especially, in workplace that sometimes maked the people to not able to careful until itu caused the single accident and this matters caused many companies used the management of human resource strategy to prevent the matters which are this matters become most of important in aassessing the people safety. Because, in other side in enable the workers get guarantee in various aspect that related with the occupations especially in this times, many companies always neglected the safety matters by using management of human resource strategy. This research is study literature thanks using the base of qualitative research and using various journals to figure out the effecitivity aspect from the implementation of management of human resource strategy which are connected with the safety of workers in every divisions. The usage of nasional journal in this research are 5 years lately and the international journals that related to the aspect of management of human resource strategy and the affect to the workers. The concluson that obtained from this research are the implementations of management of human resource strategy have been practiced in the companies especially in preventing the accident that occured in doing work